Sifat Thermal Tanah Pasiran Pantai dengan Pemberian Bahan Pengkondisi Tanah dan Biomikro pada Budidaya Tanaman Cabai (Capsicum Annuum, L) - Tri Sudyastuti; Nurdi Setyawan (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2007)
Study properties of sandy soil is important to be done to gain the good condition for growing plants. The characteristics of thermal are volumetric heat capacity of soils (Cv), thermal diffusivity of soils (DT), thermal conductivity of soils (KT) and heat flux (qh), as well as transmission of heat transfer (Q ). The objective of the research was to study thermal properties of sandy soil at coastal area by giving biomicro and soil conditioners. Treatments of irrigation used in the research were: Gembor irrigation (by using watering can) (A0) and sub surface irrigation (A1), soil conditioners used were straw (B0), 10 ton/ha of biocompost (B1), 20 ton/ha of biocompost (B2) and clerecide leaves (B3); all of those treatments were mixed with biomicro (C). The plants of chili pepper were planted in the coastal area at Kulon Progo, Yogyakarta. The results of the research showed that the treatments of irrigation and addition of soil conditioners were not significant to the alteration of soil thermal properties; heat flux (qh) influenced the production of chili pepper (Cap- sicum Annum, L); and utilizing 20 ton/ha of biocompost resulted favorable environment.ABSTRAKKajian sifat thermal tanah penting dilakukan untuk mendapatkan kondisi yang menguntungkan bagi pertumbuhan tanaman. Sifat thermal tanah tersebut meliputi kapasitas kalor volumetrik,difusitas thermal,konduktivitas thermal, fluks kalor dan laju pindah kalor. Tujuan dari penelitian ini adalah untuk mengetahui sifat thermal tanah pasiran pantai dengan pemberian bahan pengkondisi tanah dan biomikro. Perlakuan irigasi yang diberikan adalah irigasi gembor dan irigasi bawah permukaan sedangkan bahan pengkondisi tanah yaitu jerami,biokompos dan daun clereside yang semuanya dicampur dengan biomikro. Hasil penelitian menunjukkan bahwa perlakuan irigasi dan penambahan bahan pengkondisi tanah berpengaruh terhadap sifat thermal tanah dan juga diperoleh suatu model fluktuasi temperatur tanah pada tiap kedalaman dalam suatu harmonisasi sinusoidal sebagai fungsi waktu.